Changes in HIV knowledge and interest among nursing and public health students at a large Midwest University: Outcomes of implementing the National HIV Curriculum. (June 2023) - Lightner, Joseph S.; Chesnut, Steven R.; Cory, Tracy; Sellers, Sherri; Woods, Latoya; Skarbek, Anita; Willis-Smith, Nancy; Valleroy, Ella; Colbert, Sharon; Witt, Jacki
Abstract: Background: Ending the HIV epidemic requires additional healthcare and public health workers who are competent in HIV prevention and treatment. The National HIV Curriculum was developed to increase competency in HIV among healthcare workers in the US. Objectives: The purpose of the current study was to examine the impact of implementing the National HIV Curriculum (NHC) for nursing and public health students. Design: This study employed a single-arm, cohort intervention design. Setting: This study was conducted at large, public university in the Midwestern United States of America in a state noted for high HIV transmission. Participants: Undergraduate nursing, graduate nursing, and undergraduate public health students participated in this study. Methods: An online survey of nursing and public health students was conducted following implementation of the NHC at a large, public university in the Midwest. Students were assessed on knowledge and interest of HIV using a bootstrapped paired-samples t -test approach. Results: Participants ( N  = 175) were enrolled in the undergraduate nursing program ( n  = 72, 41.14 %), graduate nursing ( n  = 37, 21.14 %) public health (n = 37, 21.14 %), medicine ( n  = 10, 5.71 %), and biological, biomedical, and health sciences discipline ( n  = 19, 10.86 %). Overall, results suggest a consistent gain in knowledge of working with individuals living with HIV of 1.42 points (on a 4-point scale). About half (47.43 %) of all students increased interest to work with individuals living with HIV in the future. Conclusion: The NHC increased knowledge and interest in students across a broad range of nursing, public health, medicine, and other disciplines. This study suggests that universities can integrate the curriculum across undergraduate and graduate programs. Students at varying degree levels may benefit from the NHC. Future longitudinal studies should be conducted on the career choices of those students exposed to the NHC. Highlights: The NHC can be broadly implemented to improve HIV knowledge and interest. The NHC increased knowledge of HIV for students in nursing, public health, and more. Half (47.43 %) of all students increased interest to work with individuals living with HIV.